Resíduos de pesticidas e compostos perfluorados em águas: avaliação da exposição da população atráves do consumo - Schwanz, Thiago Guilherme (2015)
Contamination of water resources has been caused great impact to the environment. The water constitutes the greatest source of food, and its value for health is incalculable. Despite this, the presence of contaminants in water for consumption in Brazil is a topic with few researches and sources of information. The main contamination of drinking water takes place directly by man, by the abusive use of pesticides or environmental contaminants, with high bioaccumulation potential in the environment, such as perfluorinated and organochlorine compounds. These compounds are present in water in trace levels, and appropriate analytical methods in order to demonstrate the suitability of method, ensuring the reliability of the results are needed. This study presents two multi-residue methods for determination of perfluorinated compounds (PFCs) and for the determination of pesticides in samples of tap water, bottled water and groundwater collected in Brazil, Spain and France. For PFCs was used solid phase extraction automated "in line" method with direct injection of the sample coupled to mass spectrometry with detection limits between 0.15 and 8.76 ng/L, and the determination of pesticides has been carried out by solid phase extraction and analysed using different techniques of separation and ionization LC-ESI-MS/MS, GC-MS/EI and GC-MS/NCI, with detection limits between 1.02 and 48.21 ng/L. The obtained results showed that the tap water have high concentrations of PFCs, especially in Brazil, with an average of 15.83 ng/L, followed by Spain and France with 15.33 and 7.73 ng/L, respectively. For pesticide analyzes, the data found demonstrate that the groundwater obtained in Brazil showed the highest concentrations of investigated contaminants in comparison with tap and bottled water. Regarding the risk of exposure by ingestion through drinking water, PFCs represent greater danger (estimated at 54.8, 58.0 and 75.6 ng/person per day in Spain, France and Brazil) in relation to pesticides (10.23, 29.40, 30.11 ng/person per day in Spain, France and Brazil, respectively). However, despite the levels found in the investigated countries, the consumption of drinking water does not poses imminent risks to contamination associated with PFCs and pesticides.